The efficiency of stabilization exercises in patients with discopathy in the lumbar spine - Kałużna, Anna; Leszczyński, Kamil; Gałęcki, Sławomir; Płoszaj, Ola; Kałużny, Krystian; Dylewski, Michał; Hagner-Derengowska, Magdalena; Zukow, Walery (Journal of Education, Health and Sport, 2019)
Aim of the study: The aim of the study was to assess the influence of stabilization exercises on the intensity of pain and the results of the FMS test in patients with lumbar spine discopathy.Material and methods: The study included 30 patients (16 women and 14 men) aged from 25 to 68 years (x ̅=40.6±9.6) with diagnosed discopathy in the lumbar spine. Patients were qualified to be examined by a physician based on the results of imaging tests and information provided in the interview. A control group (reference group) was also created, which qualified 30 healthy people (16 women and 14 men) with average training, which were the most similar in terms of analyzed parameters to the people from the study group. The preliminary examination included functional evaluation with the FMS test and the subjective scale of VAS pain. In addition, each of the study participants filled out their own questionnaire. Then, a 14-day cycle of stabilization exercises was applied to all participants of the study. After completed rehabilitation, the patients underwent functional assessment again with the FMS test and the subjective VAS pain scale.Results: The results of the study have shown that deep muscle training has a significant effect on the reduction of pain in the lumbar spine. Targeted exercises have a positive effect on the improvement of global movement patterns. Studies show that patients' age had a significant impact on final results in FMS tests. The analysis of the conducted research shows that there are no significant differences between the test group and the control group both in the context of perceived pain and results in the final FMS tests. Studies have confirmed that undertaking regular physical activity has a positive effect on the functional status of patients.Conclusion: Stabilization training in patients with diagnosed discopathy in the lumbar spine has a positive effect on reducing back pain and functional status.